Development of microsatellite markers for the carnivorous plant Genlisea aurea (Lentibulariaceae), a species with a minute genome, using genomics data of NGS (2018)
I. Background: Genlisea aurea A.St.-Hil. is a carnivorous plant endemic species to Brazil in the Lentibulariaceae family. Very few studies have addressed the genetic structure and conservation status of G. aurea and the Lentibulariaceae. Microsatellites markers are advantageous tools that can be employed to predict the vulnerability of Lentibulariaceae species. Therefore, the development of molecular markers focusing the population analyses of Genlisea for future genetic studies and conservation actions are essential. Thus, we developed simple sequence repeats (SSRs) based on in silico analyses of G. aurea draft genome assembly. II. Methods and Results: We characterized 40 individuals from several populations and identified 12 loci that were polymorphic, with heterozygosity between 0.123 and 0.650. III. Conclusions: We demonstrated that the G. aurea SSR markers work cross-species in Genlisea filiformis, G. repens, G. tuberosa and G. violacea. These markers will be important for future population, phylogeographic and conservation studies in G. aurea and other Genlisea species.